PENGEMBANGAN INDUSTRI TAHU DAN TEMPE SEBAGAI ALTERNATIF PANGAN DI DESA CURAHMALANG KECAMATAN RAMBIPUJI KABUPATEN JEMBER - Setyowibowo, Sigit; Prasetyo, Andri (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2017)
In Curahmalang Village, Rambipuji District, there are 2 Household Industries (IRT) that is IRT tofu and IRT tempe. The amount of soybeans spent in 1 day to make tempeh 15 kg and know 6 kg. Both IRTs in their production use the traditional way. Some of the problems faced by business partners include: dependence on wood fuel, soybean peeling, pressing and packaging that still using manual tools, soybean milling must be milled to others, financial management has not been handled properly. The methods offered to overcome these problems are: (1) Human Resources Training, (2) Procurement of machines for production improvement, as for machines needed: soybean peeler machine, Pedal Sealer machine, soybean machine, presto and gas stove , manual press machine, (3) financial management training. The result of community service is a partner able to increase the number of tofu production, in a day spent 9 kg soybean and tempe 19 kg soybeans, business partners are able to record bookkeeping and financial reporting well, the partner is able to operate the machine well, training and mentoring activities responded well, as evidenced by partner involvement and active partner participation during the activity and partners understand the importance of making good and healthy tempe and tofu.